A JUDICIAL APPRAISAL ON THE BEST INTEREST OF THE CHILD STANDARD WITH REGARD TO CUSTODY AND ACCESS DECISIONS ON DIVORCE: A CONSTITUTIONAL DEVELOPMENTAL IMPRINT (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This paper does not cover all aspects of court decisions about the interests of the child. It is confined to only the best interest of the child with regard to custody decisions on divorce in Botswana jurisdictions with an imprint of South African law dynamics. Everyone that is involved in the operation of an understanding of the childs situation will benefit from what is going to be discussed in this paper. This study, however, actuates much more research into the questions of the best interests of the child. The research purports the acquisition of knowledge necessary to map out the best interests of the child standard. It does so by stressing the obsolete nature and dysfunctional practice of relics of Roman-Dutch and English common law. The study paves a new direction for determination purposes of the best interests of the child in line with constitutional imperatives or values. The research drawn the theoretical modalities from other jurisdictions, but in its practical application it resort to the Botswana judicature. Case laws of Botswana in which a constitutional imprint could be detected are, for example, Ndlovu v Macheme and Mokoti v Okatswa to name but a few. The stage is set firmly now for the protection and upholding of the best interests of the child along constitutional lines.